Aplikasi Semiotika Roland Barthes terhadap Makna Takwa dalam QS. al-Hajj [22]: 37 - falah, zulfikar; rohmah, miftahur (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2023)
AbstractThis article examines how Roland Barthes' semiotics can be used to understand the meaning of piety in QS. Al-Hajj: 37. The author's background involves the application of the definition of piety as it pertains to the role of the physical and spiritual as it has existed in humans. This study aims to ascertain the true meaning of the word "piety" as it appears in QS. Al-Hajj: 37 from a semiotic standpoint. The descriptive analysis used in this article's research was discovered through library research. Before helping one comprehend how Roland Barthes' semiotics can be applied to the meaning of piety in QS. Al-Hajj: 37. Following a description of Roland Barthes' semiotic theory, the author then discusses the meaning of "piety" in the Qur'an. When Roland Barthes' semiotics are applied to parse the meaning of piety in QS, it leads to the conclusion that there are two levels of the signification of Al-Hajj: 37. In summary, the relational interpretation between the signifiers lafaz al-taqwa and al-wiqayah has been known to be central to the denotative and connotative meanings of piety.Keywords: QS. al-Hajj: 37; Roland Barthes; Semiotics; The meaning of piety. AbstrakArtikel ini menganalisa tentang aplikasi semiotika Roland Barthes terhadap makna takwa dalam QS. al-H{ajj: 37. Latar belakang yang diambil penulis adalah implementasi makna takwa yang disebutkan telah melibatkan peran jasmani dan rohani sebagaimana telah bersemayam dalam diri manusia. Penelitian ini bertujuan untuk mengetahui makna hakiki terma takwa pada QS. al-H{ajj: 37 perspektif semiotika Roland Barthes. Metode penelitian dalam artikel ini menggunakan deskriptif analisis yang diperoleh melalui library research. Sebelum mengarah kepada pemahaman perihal aplikasinya semiotika Roland Barthes terhadap makna takwa dalam QS. al-H{ajj: 37, penulis memaparkan dahulu terkait teori semiotika Roland Barthes, dilanjutkan pembahasan terma takwa dalam al-Qur’an. Sehingga menghasilkan bahwa terdapat dua tingkatan signifikasi pada pengaplikasian semiotika Roland Barthes dalam mengurai makna takwa dalam QS. al-H{ajj: 37. Singkatnya, makna denotatif dan konotatif makna takwa telah diketahui terfokus pada interpretasi relasional antara lafaz al-taqwa> sebagai penanda dan al-wiqa>yah sebagai petanda. Kata Kunci: Makna takwa; QS. al-H{ajj: 37; Roland Barthes; Semiotika.